CULTURAL REPRESENTATION OF SPEED IN TURKEY'S 4.5G ADVERTISEMENTS - NAS, ALPARSLAN (ISTANBUL UNIV, 2017)
The notion of speed has been considered as a defining characteristic of the modern era. With the advent of technological developments in the 21st century, particularly with regard to the internet, speed has gained an even more prominent role in economic and social relations. The latest advances in mobile internet technology, for example the invention of 4G LTE, have now diffused across many countries in the world. Turkey was one of the countries to invest in this technology and 4G was introduced on April 1, 2016 under the name of 4.5G with GSM operators offering high connection speeds to attract consumers. Based on the 4.5G commercials broadcast by Turkey's three main GSM companies, Turkcell, Turk Telekom and Vodafone Turkey, this article analyzes the cultural representation of speed in these advertisements. In these advertisements, speed is conceptualized as not merely a technological phenomenon; rather it serves as a means of cultural representation attached with national narratives. Through a hermeneutical approach, this article aims to analyze the ways in which advertisements construct speed as a discourse with certain cultural representations and interpretations. This analysis suggests that the representation of speed in advertisements reproduces the subjectivities of individuals that are defined in relation to their national coexistences. Positioning the articulations of speed in these advertisements based on Paul Virilio's theory of speed, this article argues that representations of speed constitute a narrative of the nation, as theorized by Benedict Anderson's theory of imagined communities,whose members are better and faster connected to each other by means of speed.
Keywords: Advertising; Speed; Technology